Islamophobia In Indonesia’s Digital Space: A Critical Analysis Of Its Implications For Da'wah Practices And Contemporary Communication Strategies - Yusuf; Farhan Farhan; Faiz Musthofa Abbas (Penerbit Hellow Pustaka, 2026)
This research aims to critically analyze the phenomenon of Islamophobia and its implications for da’wah (Islamic outreach) practices in Indonesia within the contemporary digital context. As a form of prejudice, stereotyping, and discrimination against Islam and Muslims, Islamophobia has not only thrived in the West but has also begun to manifest in the digital spaces of Indonesia and Southeast Asia through misinformation, media framing, and the polarization of religious identity. This study utilizes a qualitative approach with a library research design, enriched by participant observation, in-depth interviews, and documentation studies. Data analysis was conducted by combining discourse analysis (to examine the construction of Islamophobic narratives) and content analysis—to identify message patterns within da’wah materials and digital media. The results indicate that Islamophobia significantly impacts the effectiveness of da’wah, particularly by fostering audience resistance, decreasing public trust, and strengthening biases within the digital ecosystem. The study finds that effective da’wah strategies in responding to Islamophobia include constructing counter-narratives based on digital education, strengthening media literacy, implementing dialogic da’wah approaches, and developing interfaith digital movements. The research implications emphasize the importance of enhancing the digital literacy and cross-cultural communication capacity of da’wah practitioners, as well as the need for adaptive and responsive policies to address the spread of Islamophobic narratives in the digital public sphere.